Rhodotor neoformans Cryptococcus , Candida albicans وضد فطرية لل Escherichia coli, Klebsiella pneumonia والسالبة لملون كرام pyogenes. , Streptococcus Staphylococcus aureus تأثير مستخلصات بعض النباتات على عدد من الجراثيم الموجبة لملون كرام - سناء جميل ثائر العلقي; عبدالرضا أكبر علوان المياح; نجوى محمد جميل علي أبو مجداد (University of Thi-Qar Journal of Science, 2019)
Antibacterial and antifungal effect of four medicinal plants extracts namely : Ocimumbasillicum L , Vinca rosea L , Eruca sativa L and Nigella sativa L were tested . Threeconcentrations 500 mg/ml , 250 mg/ ml and 125 mg/ml of 50% water – acetic acid , alcoholicand butanolic extracts were prepared and tested against the bacteria Staphylococcus aureus ,Streptococcus pyogenes , Escherichia coli and Klebsiella pneumonia , and the yeasts Candidaalbicans , Cryptococcus neoformans , Rhodotorula rubra and Trichosporon sp. Agar wellsdiffusion method was used .The results showed that the highest inhidition diameters (45.3)mm in 500 mg/ mlconcentration was for the acidic water extract of Ocimum basillicum L leaves against grampositive bacteria Streptococcus pyogenes . But it was 16.3 mm for the acidic water extract ofNigella sativa L seeds against Cryptococcus neoformans . On the other hand the butanolicextracts showed highest inhibition against Escherichia coli (19.6)mm and Rhodotorula rubra(15)mm , while the butanolic extracts of Vinca rosea L had highest inhibition againstCryptococcus neoformans (12.6)mm and Streptococcus pyogenes . (21.3)mm .Alkaloids and phenolic compounds were extracted and their biological activityeffect against above isolates were tested , and the results did not show any inhibitory againstisolates in the three concentrations 200 mg/ ml , 100 mg/ ml and 50 mg/ ml .Also no sign for any cytotoxicity against red blood cells had been shown for alltypes of extracts in concentration 500 mg/ ml .